Latvijas un ārvalstu sodu veidu un soda noteikšanas salīdzinājums noziedzīgajos nodarījumos valsts institūciju dienestā - Buglovs, Iļja (Latvijas Universitāte, 2016)
Autors veica šo pētījumu ar mērķi izpētīt noziedzīgo nodarījumu valsts institūciju dienestā teorētisko raksturojumu, to vēsturisko attīstību, analizēt kriminālsoda raksturojumu, salīdzinot to ar ārvalstu praksi, un piedāvāt lietderīgāko kriminālsoda veidu un tās noteikšanu, ievērojot ārvalstu praksi. Maģistra darba uzdevumi ir: 1) sniegt teorētisko raksturojumu jēdzienam kriminālsods, salīdzināt soda mērķus un sistēmas ar ārvalstu regulējumu; 2) noteikt korupcijas jēdzienu un koruptīvo darbību īpašības; 3) raksturot Latvijas un ārvalstu sodus par noziedzīgiem nodarījumiem valsts institūciju dienestā; 4) noteikt lietderīgāko soda veidu un ieviest novitāti sodu noteikšanā. Temata izpētes laikā tika raksturoti kriminālsodi, tā mērķi un sistēmas, ārvalstu regulējuma īpatnības un tiek piedāvāti soda noteikšanas efektīvie risinājumi.

Author performed this research with a goal to analyse the theoretical description of the criminal offence committed during the service in the governmental institutions, its historical development, to analyse description of the criminal punishment, by comparing it to a practice in foreign states and to offer a more effective type of the criminal punishment and its determination, in accordance with a foreign states practice. Tasks of this master paper are: 1) to give a theoretical definition to the term criminal punishment, to compare the purposes and systems of the criminal punishments with their foreign counterparts; 2) to determine the concept of corruption and the properties of the corruptive actions; 3) to describe the criminal punishments for the criminal offences committed during the service in the governmental institutions in Latvia and foreign states; 4) to determine the most efficient type of punishment and to provide a novelty in the process of determining the punishment. During the research of the topic the following was defined; criminal punishments, its purpose and systems and specifics of the foreign regulation. Effective solutions were offered for punishment determination.
A comparison between types of punishments and determination of the punishment in regard to the criminal acts commited in the service of govermental institution between Latvia and foreign states
Keywords: Juridiskā zinātne; Noziedzīgi nodarījumi valsts institūciju dienestā; korupcija; kriminālsods; sodu veidi; sodu noteikšana